PENINGKATAN KEMAMPUAN KALIBRASI STOPWATCH -TIMER DIGITAL 3 DIGIT DI PUSLIT METROLOGI-LIPI MELALUI METODE TOTALIZED - Hapiddin, Asep; Boynawan, A. M.; -, Ratnaningsih; Pawestri, Yulita Ika; Agmal, Swivano (Instrumentasi, 2018)
RCM-LIPI capability in the field of stopwatch-timer calibration has improved through totalized method. In this study, we compared the measurement results using the direct comparison method and the totalized method, using the same unit under test (UUT) which is the Casio 401Q21R digital stopwatch with 10-3 resolution and also with the same measuring point. Measurements in both direct and totalized calibration methods were performed with five data retrievals for each measuring point, i.e. 10 s, 20 s, 30 s, 40 s, 50 s and 60 s. The value of the measurement uncertainty has been successfully improved one order of magnitude. As a result, the human reaction time standard deviation, HRTSD: uHRTSD has significant influence to the combined uncertainty. The result of calculation of uHRTSD in calibration system using totalized method is better than calibration system using direct comparison method.